Navigating the leadership labyrinth: barriers and supports of a woman collegiate coach in a 20-year leadership role. Issue 1 (2nd January 2018) - Harvey, Stephen; Voelker, Dana K.; Cope, Edward; Dieffenbach, Kristen
Abstract: A multi-level ecological-intersectional model has been proposed as a way of understanding the intersecting social identities that shape women's experience of power and social injustices in sports coaching. Using a case study of one of the most longstanding Division I National Collegiate Athletic Association woman soccer coaches, Coach Nikki Izzo-Brown, we investigated the constructs and processes that shaped her coaching career trajectory and how the intersectional nature of these constructs and processes enabled her to navigate the leadership labyrinth. Data were generated from three semi-structured interviews and analysed abductively to form categories aligned to the four layers of the ecological-intersectional model. Barriers identified by Coach Izzo-Brown were consistent with previous literature (e.g. soft-essentialism). However, greater focus on the supportive factors perceived by Coach-Izzo-Brown (e.g. woman coaching network) can create a more inclusive culture for woman coaches. Longstanding and successful woman coaches' involvement in professional development and advocacy activities is recommended.